KEDUDUKAN ANAK TERHADAP HARTA WARISAN DALAM PERKAWINAN DIBAWAH TANGAN DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Nadia Farizha (Universitas 17 Agustus 1945 Samarinda, 2019)
AbstractThe problem in this study is the position of children born from marriage under the hands and how the rights of children to inheritance from marriage under the hands based on Law Number 1 of 1974 concerning Marriage. Underhand marriage is still happening in Indonesian society. Submarine marriage is a marriage that does not register the marriage to the authorized institution, namely the Office of Religious Affairs for Muslims and the Civil Registry for non-Muslims. In Article 2 paragraph (2) of Law Num ber 1 of 1974 it is stated that a new marriage is valid if it is carried out according to the laws of each religion and its beliefs. However, the validity of marriage in the eyes of religion and public trust needs to be ratified by the state in order to have legal force. The consequences of marriage under the hands are very bad for the wife and for children born both legally, socially and psychologically. Other problems that can be caused from marriage under the hands are the rights and obligations of husband and wife who are not guaranteed in full from the State. The provisions in Article 42 paragraph (1) of Law Number 1 Year 1974 concerning Marriage state that a legitimate child is a child born from or as a result of a legal marriage. So it can be concluded that children born from underage marriages are illegitimate children or out of wedlock children. From the results of the research discussion it is known that Based on the Decision of the Constitutional Court Number 46 / PUU-VIII / 2010 Testing of Law Number 1 of 1974 concerning Marriage to the State Constitution of the Republic of Indonesia Year 194. It is said that children born outside marriage have a civil relationship with his mother and his mother's family and with his man as his father that can be proven based on science and technology and / or other evidence so according to the law he has a blood relationship, including a civil relationship with his father's family.